Measuring rail productivity in Ireland: a note - McGeehan, Harry (Economic & Social Studies, 1995)
This note is concerned with comparing partial and total measures of productivity as they apply to Irish railways. A comparison of a partial exercise undertaken by Barrett and a total productivity approach confirms that partial measures are limited and tend to underestimate productivity growth. In addition, it is shown that cross-sectional comparisons are meaningless because of the incompatibility of international railway data. From a policy point of view little reliance should be placed on partial measures of productivity because of their propensity to misstate productivity differences across time and between firms.
Keywords: Productivity; Railways; Ireland